Pengaruh Komposisi Struktur Dewan Perusahaan terhadap Kinerja Keuangan Perusahaan Operator Seluler di Indonesia - RAYMOND, ANDREE (Jurnal Ilmu Manajemen, 2014)
This research investigated the relationship between composition of board structure and financial performance of cellular company in Indonesia. Using a balance panel of 5 cellular companies which are listed in Indonesian StockExchange, the research employed ordinary least square method. The result showed that the composition of board structure collectively have influence on financial performance of cellular company in Indonesia, refer to Return on Asset (ROA). Partially, size of board commissioner andindependence director have a significant influence on financial performance. In the other hand, independence commissioner, size of board director and female director do not have significant influence on financial performance.